Fabrication of animal shell and sugarcane bagasse particulate hybrid reinforced epoxy composites for structural applications - Oladele, Isiaka Oluwole; Taiwo, Anuoluwapo Samuel; Bello, Lateef J.; Balogun, Samuel O.; Sipho, Lephuthing Senzeni; Adelani, Samson Oluwagbenga (SAGE Publications, 2024)
This study investigated the effects of using egg and snail shells, along with sugarcane bagasse, on various properties of hybrid reinforced epoxy composites for structural applications. The particulate shells and sugarcane bagasse serve as reinforcements while the matrix consists of epoxy resin and hardener. The composites were produced using the hand lay-up technique, and the mechanical, wear and physical properties of the prepared samples were evaluated. The fractured surfaces of the samples were examined using a scanning electron microscope. The results revealed that the source of the shell had an impact on the properties of the composites as eggshell-sugarcane bagasse particulate reinforced epoxy composites exhibited improved strengths, while snail shell-sugarcane bagasse particulate reinforced epoxy composites showed improved moduli. Optimal values were obtained for flexural and tensile strengths at 15 and 18 wt%, respectively, while flexural and tensile moduli were optimal at 12 and 15 wt%, respectively. Eggshell-sugarcane bagasse particulate reinforced epoxy composites demonstrated an optimal impact strength value of 21.81 J/m2, while snail shell-sugarcane bagasse particulate reinforced epoxy composites showed optimal results in all other properties mostly at 20 wt%. Conclusively, the use of snail shell-sugarcane bagasse particles was found to be more effective than eggshell-sugarcane bagasse particles for enhancing the properties of epoxy-based composites for structural applications while particulate reinforcement content within the range of 12–20 wt% are responsible for optimum performances.
Keywords: Structural applications; polymer composites; green materials; animal shells; plant fiber